2005
DOI: 10.1007/s10725-004-7595-8
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of cDNA clones for genes that are differentially expressed during thermoinhibition in achenes of Tagetes minuta L.

Abstract: Differential display was used to isolate genes which are expressed specifically in thermoinhibited achenes of Tagetes minuta L. Of the 62 thermoinhibition-associated cDNAs identified, thirteen were cloned. Three clones for each cDNA were selected and reverse northern analysis used to confirm that all 39 clones were specific to the mRNA pool of thermoinhibited achenes only. High quality sequence data were obtained for 27 of these. Alignment of the various sequences revealed that a total of 14 different sequence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…This novel finding certainly warrants further research. In an interesting series of papers, van Staden and coworkers described an effect of some sort of memory of duration of imbibition and incubation at high temperature on germination frequency in Tagetes minuta (Forsyth & van Staden, 1983; Hills et al ., 2001; Hills et al , 2005); they first speculated that phytochrome may be involved in the response, and later found molecular evidence that thermoinhibition is under positive genetic control, in a manner analogous to embryo dormancy. We have found that the epigenetic memory of embryo development is correlated to the transcription of spruce phytochromes (Johnsen et al ., 2005a).…”
Section: Discussionmentioning
confidence: 99%
“…This novel finding certainly warrants further research. In an interesting series of papers, van Staden and coworkers described an effect of some sort of memory of duration of imbibition and incubation at high temperature on germination frequency in Tagetes minuta (Forsyth & van Staden, 1983; Hills et al ., 2001; Hills et al , 2005); they first speculated that phytochrome may be involved in the response, and later found molecular evidence that thermoinhibition is under positive genetic control, in a manner analogous to embryo dormancy. We have found that the epigenetic memory of embryo development is correlated to the transcription of spruce phytochromes (Johnsen et al ., 2005a).…”
Section: Discussionmentioning
confidence: 99%